2013
DOI: 10.1002/pd.4140
|View full text |Cite
|
Sign up to set email alerts
|

Variability of ffDNA in maternal plasma does not prevent correct classification of trisomy 21 using MeDIP‐qPCR methodology

Abstract: Overall, the variability of ffDNA and total DNA among maternal samples does not affect the correct trisomy 21 classification using MeDIP-qPCR methodology applied in peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Our group also investigated whether the variability of the fetal fraction present in maternal plasma has a negative effect in our assay’s diagnostic efficiency. Although previous reports demonstrated an effect of different fetal amounts present in maternal plasma [73,74,75], our study has shown no significant association between cffDNA fraction, absolute fetal amount or the concentration present in maternal plasma with the test result classification using our diagnostic formula [20,72]. We speculate that this is due to the fact that maternal blood contains <1% of fetal DNA [20,72] in contrast to maternal plasma, which contains ~10%–15% fetal DNA [10,76].…”
Section: Implementation Of Methyl-biomarkers In Niptcontrasting
confidence: 72%
See 2 more Smart Citations
“…Our group also investigated whether the variability of the fetal fraction present in maternal plasma has a negative effect in our assay’s diagnostic efficiency. Although previous reports demonstrated an effect of different fetal amounts present in maternal plasma [73,74,75], our study has shown no significant association between cffDNA fraction, absolute fetal amount or the concentration present in maternal plasma with the test result classification using our diagnostic formula [20,72]. We speculate that this is due to the fact that maternal blood contains <1% of fetal DNA [20,72] in contrast to maternal plasma, which contains ~10%–15% fetal DNA [10,76].…”
Section: Implementation Of Methyl-biomarkers In Niptcontrasting
confidence: 72%
“…The efficiency of the MRED assays depends on the purity of the sample, and for this reason, they require high purity and high integrity samples [90]. Additionally, MRED assays require fairly high quantities of starting material, which is a restriction to its implementation in plasma samples, because not only the target fetal DNA sequences are of a low amount, but also the total plasma DNA is very low (around 10 ng/4 mL plasma) [20]. An additional drawback of the assay is that it can only evaluate the methylation status of a specific and very limited number of genomic sequences.…”
Section: Evaluating the Efficiency Of Methylation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fourth study 64 , cfDNA testing was performed prospectively in 333 singleton pregnancies at 14 (range, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] weeks. The test did not provide a result in 1.2% of cases and there was no follow-up in 5.5% of cases.…”
Section: Nature Of the Studiesmentioning
confidence: 99%
“…The MeDIP assay can tolerate sample impuritiesand thus, no prior sample purification is required -and is not affected by the amount of ccffDNA or fetal gender or the presence of informative polymorphic sites as it may happen to SNP-related methods [50,51]. It can be applicable for low starting DNA templates, generating sufficiently enriched outputs, a development that renders possible its implementation with plasma samples [52].…”
Section: Epigenetic-based Nipt Approachesmentioning
confidence: 99%